TO STUDY THE FEATURES OF CLINICAL CHANGES IN THE ORGANS OF THE ORAL CAVITY IN DISEASES OF THE DIGESTIVE SYSTEM - Khojaeva Shakhnoza Shukhratovna (Scholar Express Journals, 2023)
This paper provides clinical examples of restoring the color and shape of the frontal group of teeth. Modern means and methods of whitening are used, as well as composite materials for the restoration of the crown part.
Keywords: kappellaners; generalization of the process; purulent-inflammatory diseases